Navigating by Judgment: Organizational Structure, Autonomy, and Countr y Context in Delivering Foreign Aid - Honig, Daniel (2015)
This dissertation examines when initiatives by International Developme nt Organizations (IDOs) are more, and less, successful. The core argum ent is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most ef fective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public mana gement and bureaucracy – would predict, with better performance result ing from less control. In the delivery of foreign aid the costs of mon itoring to the principal are often overshadowed by the deleterious eff ects of the monitoring itself. The core of the argument is that develo pment implementation requires soft information, tacit knowledge, and f lexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in en vironments that are uncertain or difficult to understand from the outs ide and tasks where outputs are difficult to observe and/or poorly cor related with long term intervention goals. Insecure political authoriz ing environments which constrain the autonomy of IDOs prevent these or ganizations from Navigating by Judgment in situations where this is th e best strategy. Empirically, this dissertation examines a cross-IDO d ataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) a nd the UK’s Department for International Development (a higher autonom y IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT